Effect of storage temperature and packing materials on seed germination and seed storage behavior of Schefflera abyssinica - TURA BAREKE; ADMASSU ADDI; KASIM ROBA; TOLERA KUMSA (Nusantara Bioscience, 2022)
Abstract. Bareke T, Addi A, Roba K, Kumsa T. 2022. Effect of storage temperature and packing materials on seed germination and seed storage behavior of Schefflera abyssinica. Nusantara Bioscience 14: 141-147. Knowledge of seed storage behavior is crucial for developing appropriate ex-situ conservation strategies. The main objective of this study was to determine the seed storage behavior of Schefflera abyssinica (Hochst. ex A. Rich.). A factorial combination of three temperatures (-10, 0, and 22°C) levels, two types of packing containers (polythene bag and aluminum bag), and eight periods of storage (0, 30, 60, 90, 120, 150, 180 days, and for a year) level was used to determine the germination capacity and storage behavior of the seeds. Accordingly, seed storage temperatures and storage period (up to 1 year) have a significant effect on the germination (p<0.01) of S. abyssinica. The highest average germination percentage of S. abyssinica seeds was obtained after 2 months of storage under all conditions. The seed storage period influences the germination of S. abyssinica by 47.8%. The germination percentages of S. abyssinica seeds have shown significant differences in storage temperatures. Seeds stored at -10°C showed the highest germination percentage in all storage periods compared to the two storage temperatures. Generally, the highest germination capacity of S. abyssinica seeds was between 7% and 9% moisture content after 60 and 90 days of storage. Packing materials have no significant difference in the survival of seeds. No stored seeds germinated after one year of storage at room temperature, 0°C, and -10°C. Based on the definition of seed storage behavior, we conclude that seeds of S. abyssinica have intermediate storage.